Abstract 4140: Secreted protein acidic and rich in cysteine (SPARC) promotes mammary tumor growth and dissemination through immune and non-immune mediated mechanisms - Güttlein, Leandro N.; Benedetti, Lorena G.; Spallanzani, Raúl G.; Rotondaro, Cecilia; Raffo Iraolagoitia, Ximena L.; Sganga, Leonardo; Salvatierra, Edgardo; Llera, Andrea S.; Zwirner, Norberto W.; Podhajcer, Osvaldo L. (Cancer research (Chicago, Ill.), 2016)
Secreted protein and rich in cysteine (SPARC) is a matricellular glycoprotein which has been extensively associated with breast cancer progression, both in human tumors and in experimental models. However, the molecular mechanisms responsible for this effect are still unclear in particular because most studies were performed in immunocompromised nude mice. We undertook a comprehensive study of SPARC role in this disease by using the highly metastatic and poorly immunogenic 4T1 and LM3 mammary tumor cells syngeneic in Balb/c mice. Knock down of SPARC expression using a targeted shRNA in both cell lines greatly reduced primary tumor growth and completely obliterated the establishment of metastatic foci in lung. We performed global gene expression analysis comparing primary tumors and metastatic foci of control 4T1 cells with those arisen from shRNA-treated, SPARC-deficient 4T1 cells. From these studies, a potential role of the inflammatory/immune response in controlling tumor evasion and metastasis, more specifically through genes associated with the prostaglandin pathway, was suggested. As we explored this hypothesis, we observed that knock down of SPARC expression in 4T1 3D spheroids, but not in 2D monolayers, downregulated COX-2 mRNA and protein levels. Moreover, exogenous addition of SPARC in SPARC-deficient spheroids of 4T1 and MDA-MB-231 human breast cancer cells increased COX-2 expression. Interestingly, the re-expression of COX-2 in SPARC-deficient 4T1 cells partially restored the in vivo primary tumor growth with no effect on the establishment of metastatic foci. COX-2 plays an important role in inducing myeloid-derived suppressor cells (MDSCs, CD11b+Gr-1+ cells), which promotes breast cancer outgrowth through immunosuppression. Flow cytometry analyses demonstrated that SPARC-deficient 4T1 tumor-bearing mice exhibited reduced levels of CD11b+Gr-1+ cells compared to control 4T1 tumor-bearing mice in the spleen (6,9±3,2 vs. 25,3±2,0 p<0,001), lungs (0,7±0,2 vs. 6,2±0,9 p<0,001) and bone marrow (48,0±6,4% vs. 62,1±5,3 p>0,05). COX-2 re-expression restored systemic MDSCs expansion in SPARC-deficient 4T1 tumor-bearing mice. The present data suggest that COX-2 expression is under SPARC control in breast cancer cells; moreover, COX-2 could mediate SPARC effects on tumor evasion from immune surveillance. Citation Format: Leandro N. Güttlein, Lorena G. Benedetti, Raúl G. Spallanzani, Cecilia Rotondaro, Ximena L. Raffo Iraolagoitia, Leonardo Sganga, Edgardo Salvatierra, Andrea S. Llera, Norberto W. Zwirner, Osvaldo L. Podhajcer. Secreted protein acidic and rich in cysteine (SPARC) promotes mammary tumor growth and dissemination through immune and non-immune mediated mechanisms. [abstract]. In: Proceedings of the 107th Annual Meeting of the American Association for Cancer Research; 2016 Apr 16-20; New Orleans, LA. Philadelphia (PA): AACR; Cancer Res 2016;76(14 Suppl):Abstract nr 4140.